Detection of human papillomavirus DNA in pterygia from different geographical regions. Issue 7 (1st July 2003) - Piras, F; Moore, P S; Ugalde, J; Perra, M T; Scarpa, A; Sirigu, P
Abstract : Background/aims: The aetiology and pathogenesis of pterygia remain unclear and the involvement of human papillomavirus (HPV) is controversial. 41 pterygia from two geographic locations were evaluated for the presence of HPV DNA. Methods: 41 pterygium biopsies (17 from Italy and 24 from Ecuador) were analysed using the L1C1 and PU-1ML primer sets by polymerase chain reaction (PCR) and DNA sequence analysis. Results: 22 of the 41 pterygia (54%) were positive for HPV, including all 17 Italian cases and 5/24 (21%) Ecuadorean cases. DNA sequencing of the 22 positive cases showed that 11 were HPV type 52, four were type 54, five were cand HPV90, and two of unknown genotype. Conclusions: The major differences in the frequency of HPV in geographically distant populations might suggest a possible explanation for the vast differences in the reported detection rates. Three subtypes of HPV were found in this sample of pterygia. None the less, these results suggest that HPV may have a pathogenic role in pterygium.